MEDIA PROMOSI VIRTUAL REALITY PANTAI TANJUNG KALIAN SEBAGAI IKON WISATA BANGKA BELITUNG - kelvin hamdani; Bobby Halim; Mukhsin Patriansah (Penerbit dan Percetakan, CV. Picmotiv, 2023)
Abstract : Bangka Belitung has one of the unique beach tourism such as Tanjung Kalian Beach. Tanjung Kalian Beach is a natural tourism and historical tour in Bangka Belitung Province, precisely on the island of Bangka. The uniqueness of Tanjung Kalian Beach has a lighthouse icon. A lighthouse is a tower building with a light source at the top to aid ship navigation. The lighthouse is also a silent witness to the occurrence of World War II at Tanjung Kalian Beach. To preserve the history of the lighthouse and World War II and provide information on the beauty of Tanjung Kalian Beach. So, it is necessary for designers to promote Tanjung Kalian Beach as a tourist icon of Bangka Belitung. This design method uses Design Thinking. Design thinking is a tool used in a problem solving, in the process using 5W+2H analysis. The main design media uses documentary videos that are packaged using virtual reality. The design of the Tanjung Kalian Beach promotion was carried out with the aim that the public would become familiar with Tanjung Kalian Beach and become a reference for people's holiday spots to Tanjung Kalian Beach so that it would be known to the public as a tourism icon of Bangka Belitung.